2009
DOI: 10.1186/1745-6215-10-104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial to assess the effect of physical exercise on endothelial function and insulin resistance in pregnant women

Abstract: BackgroundPreeclampsia (PE) is a common maternal disease that complicates 5 to 10% of pregnancies and remains as the major cause of maternal and neonatal mortality. Cost-effective interventions aimed at preventing the development of preeclampsia are urgently needed. However, the pathogenesis of PE is not well known. Multiple mechanisms such as oxidative stress, endothelial dysfunction and insulin resistance may contribute to its development. Regular aerobic exercise recovers endothelial function; improves insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
(31 reference statements)
1
16
0
1
Order By: Relevance
“…So one might speculate that the increase of VO2max observed in the group assigned to the program of aerobic exercise could have a beneficial effect in fetal development. [46][47][48][49][50] In conclusion, the results of the present study demonstrate that a controlled program of aerobic exercise during pregnancy improves endothelial function and cardiorespiratory fitness. It remains to be demonstrated if exercise interventions could be a novel alternative in the prevention of complications associated with endothelial dysfunction during pregnancy.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…So one might speculate that the increase of VO2max observed in the group assigned to the program of aerobic exercise could have a beneficial effect in fetal development. [46][47][48][49][50] In conclusion, the results of the present study demonstrate that a controlled program of aerobic exercise during pregnancy improves endothelial function and cardiorespiratory fitness. It remains to be demonstrated if exercise interventions could be a novel alternative in the prevention of complications associated with endothelial dysfunction during pregnancy.…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, it was observed that the VO 2max diminishes progressively during the pregnancy. So one might speculate that the increase of VO 2max observed in the group assigned to the program of aerobic exercise could have a beneficial effect in fetal development 46–50 …”
Section: Discussionmentioning
confidence: 99%
“…Recruitment took place in three Prenatal Hospital Care units in different regions of Cali, Colombia during ten months of 2008 and the first months of 2009. Interested women eligible for the present study were invited to a pre-test, including interview and assessments at the Cañaveralejo Hospital, Siloé Healthcare Center, Meléndez Healthcare Center, and the Biochemistry Laboratory at Universidad del Valle in Cali, Colombia 11 . Pregnant women were included if they were: nulliparous women who had not participated in a structured exercise program, 16-30 years of age, with live fetus at the routine ultrasound scan and a normal pregnancy and gestational age of 16 to 20 weeks.…”
Section: Participantsmentioning
confidence: 99%
“…The study was performed in conjunction with a controlled, randomized clinical trial, the objective of which was to evaluate the effectiveness of a program of aerobics of moderate intensity for sedentary pregnant women with respect to the outcome of the pregnancy, physical capacity and maternal cardiorespiratory parameters during labor and childbirth. Details on the intervention and the main results of this study are already published elsewhere (Trial registration: NCT00741312) 11 . For this reason, we chose a sample size of at least 70 pregnant women to ensure that mean utility estimates would have a margin of error not greater than 7% at a 95% confidence interval.…”
Section: Participantsmentioning
confidence: 99%
“…23 Sin embargo, en embarazadas el efecto del ejercicio físico aeróbico sobre el consumo de oxígeno no está claramente demostrado. 24 Nuestros resultados en cuanto al incremento del consumo indirecto de oxígeno coinciden con los reportados por Dwarkanath et al, 25 quienes observaron en las mujeres no embarazadas con un nivel alto de actividad física valores mayores de VO 2max . Por el contrario, Heenan et al 26,27 no observaron diferencias significativas en el VO 2max , el umbral ventilatorio y la eficiencia de trabajo entre dos grupos de embarazadas, en las que uno realizó ejercicio aeróbico y el otro no.…”
Section: Discussionunclassified